FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI CABAI MERAH BESAR DI DESA RESPEN TUBU KECAMATAN MALINAU UTARA KABUPATEN MALINAU PROVINSI KALIMANTAN UTARA (Factors Affecting the Production of Large Red Chilli Farming in Respen Tubu Village, North Malinau District, Malinau Regency) - Dewi Ryanthy; Markus Patiung; Ristani Widya Inti (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2024)
Large red chili is one of the horticultural commodities that is needed by many people withconsumption levels that tend to increase every year. Therefore, it is necessary to makevarious efforts to increase the production of large red chili. This study aims to analyze thefactors that affect the production of large red chili farms in Respen Tubu Village, NorthMalinau District, Malinau Regency. This research was conducted in Respen Tubu Village,North Malinau District, Malinau Regency. The sampling method was carried out as a wholeof the objects studied, by taking all existing populations, namely as many as 80 members of farmer groups. This study uses a data analysis method, namely Multiple Linear Regression Analysis The results of the analysis showed that the production factors that affect red chili production in Respen Tubu Village, North Malinau District, Malinau Regency are, labor while seeds, ZA Fertilizer, KCL Fertilizer, and Urea Fertilizer have no effect on the production of large red chili. To increase the production of large red chilies in Respen Tubu Village, farmers need to pay attention to the use of production factors and requirements in large red chili farming in order to increase production, such as expanding land and maximizing land use and paying attention to the number of crops.Keywords: Big Red Chili, North Malinau Tubu Respen, Production Factor